INDONESIAN HALAL FOOD INDUSTRY: DEVELOPMENT, OPPORTUNITIES AND CHALLENGES ON HALAL SUPPLY CHAINS - Peristiwo, Hadi (UIN Walisongo Semarang, 2019)
This paper aims to determine the development, opportunities and challenges of the halal supply chain in the Indonesian halal food industry. The method used is descriptive qualitative method. A qualitative approach is a procedure that produces descriptive data in the form of written or spoken words from people and the observed behavior of giving a comprehensive picture. The type of research is descriptive with the aim that researchers can reveal facts, phenomena, and conditions present. Research results show in the era of the halal food chain and halal science as it is today, competition for halal food needs is higher than overseas, therefore halal food companies must maintain production, with the application and other technology companies must respond to consumers faster. The market potential for the halal food industry in Indonesia is developing rapidly. Over the past few years, Indonesia is ranked first as Halal food consumers in the world. Nevertheless, the market potential is very the amount has not been able to be used optimally by the government to improve Indonesia's economy. Maintaining the quality of halal food products is one way to compete with other countries in the halal food industry.